Energy loss in systems of stacked rocking bodies - Chatzis, M; Garcia Espinosa, M; Needham, C; Williams, M (American Society of Civil Engineers, 2018)
Free-standing bodies, which rock in response to dynamic base excitations, can be found in a wide range of applications. There are many instances, for example a museum artifact seated on a support pedestal, where both the object and its support are free-standing, resulting in a dynamic system where both bodies can rock with respect to their contact interfaces. This paper analyzes the rich dynamics of systems of two stacked rocking bodies. It focuses on the location of the resultant impulses between bodies during impact, considering their effect on the overall stability of the system. The widely-used assumption that the impulses occur at the future rocking corners is shown to be the least conservative scenario and often leads to underestimating the likelihood of failure. The optimum configuration of two stacked blocks is found to be highly sensitive to the characteristics of the input motion and to the location of the impulses.